2020
DOI: 10.1111/odi.13510
|View full text |Cite
|
Sign up to set email alerts
|

High‐risk human papillomavirus in patients with oral leukoplakia and oral squamous cell carcinoma—A multi‐centre study in Sweden, Brazil and Romania

Abstract: Objectives Although causal associations between oral leukoplakia (OL), oral squamous cell carcinoma (OSCC) and high‐risk human papillomavirus (HR‐HPV) have been speculated upon in several reports, conclusive evidence has not been presented. This study investigates whether the number of cases of HR‐HPV in OL has increased over time and whether the prevalence of HR‐HPV‐positive OL differs in various parts of the world. Patients and Methods A total of 432 patients with OL from Sweden, Brazil and Romania were anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 33 publications
0
19
0
Order By: Relevance
“…It is likely prudent, however, to advise patients with OLK to refrain from using high alcohol‐containing mouthwashes (McCullough & Farah, 2008), given results of a large retrospective investigation which showed potential risks for head and neck cancer subsites and in long‐term and frequent users of mouthwash (Boffetta et al., 2016). HPV has not been found to be a substantial contributor to induction of OLK, with some studies failing to detect it in a wide variety of populations over a long timeframe (Sundberg et al, 2019; Sundberg et al, 2020), while others have shown only very low positive rates of detection (<5%) with no difference to normal or OSCC samples (Della Vella et al, 2020; Yang et al, 2019). Pooled estimates of HPV prevalence in OLK (20.2%) and PVL (24.7%) were no different to other potentially malignant conditions, such as oral lichen planus (23.0%) and oral submucous fibrosis (28.6%), and were independent of OED (de la Cour, Sperling, Belmonte, Syrjänen, & Kjaer, 2020).…”
Section: Clinical and Histopathological Determinants Of Malignant Tramentioning
confidence: 99%
See 1 more Smart Citation
“…It is likely prudent, however, to advise patients with OLK to refrain from using high alcohol‐containing mouthwashes (McCullough & Farah, 2008), given results of a large retrospective investigation which showed potential risks for head and neck cancer subsites and in long‐term and frequent users of mouthwash (Boffetta et al., 2016). HPV has not been found to be a substantial contributor to induction of OLK, with some studies failing to detect it in a wide variety of populations over a long timeframe (Sundberg et al, 2019; Sundberg et al, 2020), while others have shown only very low positive rates of detection (<5%) with no difference to normal or OSCC samples (Della Vella et al, 2020; Yang et al, 2019). Pooled estimates of HPV prevalence in OLK (20.2%) and PVL (24.7%) were no different to other potentially malignant conditions, such as oral lichen planus (23.0%) and oral submucous fibrosis (28.6%), and were independent of OED (de la Cour, Sperling, Belmonte, Syrjänen, & Kjaer, 2020).…”
Section: Clinical and Histopathological Determinants Of Malignant Tramentioning
confidence: 99%
“…HPV has not been found to be a driver of oncogenesis or a contributor to MT of OLK, although overexpression of p16INK4A in dysplastic epithelium has been noted (Wu et al, 2019), but found not to be HPV‐dependent (Tomo et al, 2020). Furthermore, p16 is not a reliable biomarker for HPV infection in patients with OLK or OSCC (Sundberg et al, 2019; Sundberg et al, 2020).…”
Section: Clinical and Histopathological Determinants Of Malignant Tramentioning
confidence: 99%
“…Among these 26 manuscripts, 13 were excluded due to not pertinent full text (11 studies with no OLK subdivision in a study group or no subdivided outcomes, even the number of OLK cases was known, 2 studies with no OLK). There were 6 articles with casecontrol studies [5][6][7][8][9][10], 7 articles with cross-sectional studies [11][12][13][14][15][16][17] and no articles with cohort studies.…”
Section: Resultsmentioning
confidence: 99%
“…Subsequently, outcomes were analysed to estimate overall prevalence in the group without and with dysplasia. Dysplasia of leukoplakia was mentioned in 7 articles [5,7,9,11,14,16,17]. Four articles were excluded due to lack of HPV detected in some study or not-subdivid- There were limitations of some analysed studies associated with HPV-DNA detection: high risk of false outcomes due to non-quantitative PCR and PCR-product visualization on gel [5,7,8,13,14], and a very small group of OLK [6,10,13].…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have implicated tobacco use in the aetiology of OL. In addition, excessive consumption of alcohol and infection with human high-risk papillomavirus have been proposed to play roles in the development of OL [3,6], with the latter showing different infection prevalence rates [7].…”
Section: Introductionmentioning
confidence: 99%